Asymptotically normal estimates of solutions of a system of algebraic equations. I - Girko, V. L. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Statistical estimates with respect to observations over the coefficient matrix of the system of equations are found for the regularized solutions of systems of linear algebraic equations. Under certain conditions, it is proved that this estimate is asymptotically normal.